How do you complete the square?

Completing the square is often useful when solving equations! An example: x+6x-7=0. Step 1) We want to move the constant to the right hand side: x2+6x=7. Step 2) Now, add the square of the coefficient of x on to both sides: x2+6x+32=7+32 -> x2+6x+9=16. Step 3) Factorise the left hand side: (x+3)2=16. Step 4) Square root the equation and solve: x+3=+/-4  -> x=-3+/-4.

Answered by Lisa W. Maths tutor

3505 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Solve simultaneously: x + y + 3 = 0 and y = 2x^2 +3x - 1


Differentiate y = x^2 - 2x-3 + e^3x + 2ln(x)


Find the factors of x^3−7x−6


How to differentiate y=(x^2+4x)^5


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences